Efektivitas Mediasi Online dalam Penyelesaian Sengketa Perdata: Perspektif Hukum Acara dan Etika Profesi. (Analisis normatif terhadap mekanisme mediasi daring yang kini diakomodasi oleh MA.) - Athaya Alghaniyyu Rahmatulloh; Sidi Ahyar Wiraguna (Ar-Rasyid: Jurnal Publikasi Penelitian Ilmiah, 2025)
The development of information technology has encouraged the Indonesian judicial system to adapt through the implementation of online mediation in resolving civil disputes. This policy is based on Supreme Court Regulation (PERMA) No. 1 of 2016 and the judiciary’s digitalization program as a form of modernization in legal services. This study aims to analyze the effectiveness of online mediation from the perspective of civil procedural law and professional ethics, in order to evaluate its conformity with the principles of justice, confidentiality, and voluntariness. This research employs a normative juridical method using statutory and conceptual approaches through a literature review of relevant laws, doctrines, and court decisions. The findings indicate that online mediation has obtained strong legal legitimacy and offers potential to enhance the efficiency of dispute resolution. However, its effectiveness remains influenced by technical barriers, digital literacy disparities, and the ethical responsibility of mediators and advocates in maintaining integrity and data confidentiality.